Municipal wastewater treatment via co-immobilized microalgal-bacterial symbiosis: Microorganism growth and nutrients removal. (November 2017) - Shen, Yu; Gao, Jingqing; Li, Linshuai
Highlights: P. putida and C. vulgaris were co-immobilized for wastewater treatment. The growth of both microorganisms was enhanced mutually in co-immobilized treatment. Co-immobilized treatment showed better performance than single-species treatments. A HRT of 24 h at the OLR of 1159.2 mg COD L −1  d −1 was optimal to treat wastewater. Abstract: A symbiotic microalgal-bacterial system may be an optional technology for wastewater treatment. In this study, co-immobilized of a bacterium isolated from a municipal wastewater treatment plant ( Pseudomonas putida ) and a microalgae Chlorella vulgaris was used in the study of cell growth and nutrient removal during wastewater treatment under batch and continuous culture conditions. Under batch culture conditions, co-immobilization treatment significantly increased the cell density of C. vulgaris and P. putida compared with other treatments. The co-immobilized treatment also showed higher removal of ammonium, phosphate and COD than any single treatment, indicating that the nutrient uptake capability of C. vulgaris and P. Putida was mutually enhanced mutually. When tested in continuous mode, the treatment with a hydraulic retention time of 24 h at the organic load rate of 1159.2 mg COD L −1  d −1 was most appropriate for wastewater treatment.